PENGAWASAN DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA JAMBI DALAM PENDISTRIBUSIAN LPG SUBSIDI 3 KG DI KECAMATAN PAAL MERAH KOTA JAMBI - Yuli Rahmawati; Citra Darminto; Dinda Rosanti Salsa Bella (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the supervision carried out by the Jambi City Department of Trade and Industry in the distribution of 3 kg subsidized LPG in Paal Merah District. The study is based on Regional Regulation No. 10 of 2013 concerning the control and supervision of LPG distribution. A descriptive qualitative method was employed using observation, interviews, and documentation. The analysis adopted Robbins and Coulter’s supervision stages: setting standards, measurement, comparison, and corrective action. The findings indicate that supervision has been implemented through socialization, monitoring, and guidance for agents and distributors. However, it remains ineffective due to mistargeted distribution, the use of subsidized LPG by higher-income households, limited human resources, and non-compliance by some distributors. These issues have generated public complaints. The study concludes that stronger supervision and stricter enforcement are required to ensure effective and targeted LPG distribution.